Bone Marrow Adipose Tissue: Formation; Function; and Impact on Health and Disease - Erica L. Scheller (Frontiers Research Topics, 2017)
Adipocytes are a major component of the bone marrow, accounting for up to 70% of total bone marrow volume in healthy humans. Indeed, this bone marrow adipose tissue (often referred to as 'MAT' or 'BMAT') accounts for at least 5% of total adipose tissue mass in lean, healthy humans, suggesting a role in normal physiology and development. Bone marrow adiposity further increases with ageing and in diverse clinical conditions, including major public health challenges such as osteoporosis. Yet despite this abundance and compelling clinical potential, bone marrow adipocytes have received surprisingly little attention from the biomedical research community. Thankfully, this is now beginning to change. Research over the past decade has begun to increase our knowledge of BMAT, including the conditions associated with altered bone marrow adiposity and the potential physiological and pathological functions of bone marrow adipocytes. The articles within this e-Book highlight many of these recent developments, underscoring our increasing knowledge of BMAT formation and function; showcasing emerging techniques for basic and clinical BMAT analysis; and highlighting key questions and future directions for this burgeoning and increasingly diverse field. The editors would like to express their thanks to the authors for contributing the articles within this e-Book; to the senior editors at Frontiers in Endocrinology for their guidance; and to the staff at Frontiers for their helpful input throughout.